PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN SEBAGAI VARIABEL KONTROL - Jessica Goldwin; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to obtain empirical evidence on the influence of applying corporate governance to firm performance. Corporate governance was measured by using CGPI score, while firm performance was measured by using ROE. This study also used firm size, firm age and financial crisis as control variables. This study was conducted on companies that obtain CGPI ranking from 2001-2015 with a sample of 248 observations. The result of this study showed that corporate governance had positive and significant affect on firm performance and firm age had negative and significant affect on firm performance. The result of this study also showed that firm size and financial crisis had no significant affect on firm performance.